2005
DOI: 10.1017/s0016672305007652
|View full text |Cite
|
Sign up to set email alerts
|

Further mapping of quantitative trait loci for postnatal growth in an intersubspecific backcross of wild Mus musculus castaneus and C57BL/6J mice

Abstract: We regret that in the article by Akira Ishikawa et al. in Genetical Research (2005) Vol. 85, No. 2, pp. 127–137, Fig. 1 on page 131 should have been reproduced in colour, not in black and white. Please find the correct version below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…These findings suggest a chromosomal region with a predominantly additive effect on the whole pre-adult growth phase in mice. In addition, we confirmed the observations of Ishikawa et al (2005) and Vaughn et al (1999) that postnatal and later growth are regulated in part by different genes. The multiple effect on Chr 1 was predominantly made up of body weight at 4, 5 and 6 weeks, while on Chr 3 only bw2 and bw3 contributed significantly to the detected effect.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These findings suggest a chromosomal region with a predominantly additive effect on the whole pre-adult growth phase in mice. In addition, we confirmed the observations of Ishikawa et al (2005) and Vaughn et al (1999) that postnatal and later growth are regulated in part by different genes. The multiple effect on Chr 1 was predominantly made up of body weight at 4, 5 and 6 weeks, while on Chr 3 only bw2 and bw3 contributed significantly to the detected effect.…”
Section: Discussionsupporting
confidence: 89%
“…However, in most studies mice at later ages than ours were examined or measurements were not made at weekly intervals, which makes a comparison with our data problematic. In contrast, Ishikawa et al (2005) reported a single QTL on Chr 2 affecting the whole investigated growth phase of 3 to 10 weeks. This chromosomal region overlapped with the multiple-trait QTL which Table 4.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Our previous genome-wide QTL studies revealed 24 QTLs for postnatal body weight and growth in an intersubspecific backcross mouse population between C57BL/6J (B6), a common inbred strain, and wild Mus musculus castaneus mice captured in the Philippines (Ishikawa et al 2000(Ishikawa et al , 2005Ishikawa & Namikawa 2004). We developed the congenic strain B6.Cg-Pbwg1 on the B6 genetic background with a 44.1-Mb wildderived genomic region containing Pbwg1, the most potent growth QTL on mouse chromosome 2 among the 24 QTLs (Ishikawa et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Body weight and fatness are quantitative traits of agricultural and medical importance and they have long been used in the mouse as archetypal model quantitative traits since the 1940s (Eisen 2005). In our previous genome-wide QTL analyses, 24 QTLs for body weight and growth at 3-10 weeks after birth have been mapped on 13 mouse chromosomes in an intersubspecific backcross population between wild subspecies mice, Mus musculus castaneus, captured in the Philippines and the common inbred strain C57BL/6J (Ishikawa et al 2000(Ishikawa et al , 2005Ishikawa & Namikawa 2004). Among the 24 QTLs mapped, two QTLs, named Pbwg9 and Pbwg16, are localized on chro-mosome 10.…”
Section: Introductionmentioning
confidence: 99%